Green Protocols in Heterocycle Syntheses via 1,3-Dipolar Cycloadditions - Martina, Katia; Tagliapietra, Silvia; Veselov, Valery V.; Cravotto, Giancarlo (Frontiers in Chemistry, 2019)
The aim of this review is to provide an overview of green protocols for the organic synthesis of heterocycles via 1,3-dipolar cycloaddition. Particular attention has been devoted to the use of green solvents; reactions performed in ionic liquids, fluorinated solvents and water have been included. Also explored are several protocols that make use of catalyst-free reaction conditions, the use of microwave irradiation and activation by light exposure. Improvements over commonly used organic solvents will be underlined in order to highlight environmental protection aspects and enhancements in regio- and stereoselectivity.